Praxis et énonciation : Greimas héritier de Saussure - Fontanille, Jacques (Estudos Semióticos, 2018)
In the characteristic dichotomies of structuralism, praxis is on the side of speech, process, discourse, enunciation and social change, and even diachrony in general. It would thus be opposed to the other side of the dichotomies: language, system, synchrony, semio-narrative structures. Yet, from Saussure to Greimas, praxis is precisely responsible for the permanent and imperceptible evolutions of the system and the semio-narrative structures. It is therefore necessary to grasp praxis from another point of view, in order to understand in what it is fully concerned with the system: the point of view of semiosis, produced by praxis. After having evoked the questions relating to the instance to which this praxis can be attributed, a nonconscious or conscious, massive or individual instance, we shall show why it is at least necessarily impersonal and reflexive.